Spa social responsibility as a quality signal: building customer loyalty through ethical and sustainable practices - Pinthong, Chitlada; Inprasertkul, Thanapol; Rattanopas, Chairat; Fakfare, Pipatpong; Han, Heesup; Chua, Bee Lia (Elsevier Ltd, 2026)
Drawing on signaling theory and the Stimulus-Organism-Response (S-O-R) framework, the research examines how specific dimensions of social responsibility, such as eco-friendly products, sustainable design, waste management, and certification standards shape consumer perceptions. Using Generalized Structured Component Analysis with Measurement Errors (GSCAM) together with necessary condition analysis (NCA), the study identifies both sufficient and necessary spa social responsibility components that drive attitudinal and behavioral outcomes. Key findings reveal that certain sustainability practices are essential for forming positive attitudes, which, in turn, are critical for customer loyalty. Conversely, promotional logistics and cultural sustainability were found to be less influential or insufficient on their own. The results provide a comprehensive theoretical contribution to socially responsible signaling and offer practical insights for spa managers seeking to enhance competitiveness through authentic and strategically communicated social responsibility initiatives.